Bibliometric analysis of research trends of physical activity intervention for autism spectrum disorders - Wang, Shimeng; Chen, Dandan; Yoon, Inae; Klich, Sebastian; Chen, Aiguo (Frontiers in Human Neuroscience, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by social impairment, restricted interests, and repetitive stereotyped behaviors. At present, its pathogenesis has not been fully understood. Various methods are used for clinical treatment and intervention, among which physical activity (PA) intervention also has obvious effect. This study used bibliometric methods and visual analysis methods to analyze 885 studies of PA intervention in ASD from 2003-2022 in the Web of Science database in order to provide theoretical support for the follow-up research on the effect of PA with ASD. The main findings of this study are as follows. Firstly, the literature on PA interventions in ASD research showed a growing trend. The leading institution in this field is the University of Delaware; Forming a core group of authors represented by authors such as Sean Healy and Carol Curtin et al. Secondly, the research focus of this research area mainly includes PA interventions for children and adolescents with ASD. PA can improve symptoms such as stereotyped behaviors and motor function in patients with ASD, as well as reduce childhood obesity rates and improve quality of life. Thirdly, skill, youth, prevalence, and meta-analysis systematic reviews were found. It is the long-term concern and focus of researchers. In conclusions, the current research is only a short term analysis, and it is not possible to verify the long-term effect, thus future data analysis should evaluate and explore the long-term effects of PA interventions on ASD including cohort and longitudinal study types focused on rehabilitation of patients with ASD. Moreover, testing the sustainability of benefits for children with ASD, and constructing a multidimensional integrated exercise integrated intervention model will be the main direction for future research in this field.